A suitcase full of ghosts - Stilton, Geronimo (Creepella von Cacklefur, 2015)
"Creepella is about to interview the famouse Hector Spector, who has come to Mysterious Valley with his Galloping Ghost Circus. But before she can, she has a mystery on her paws--someone is playing tricks and making messes all over Cacklefur Castle! Can she put a stop to these ghastly gags?"--P. [4] of cover.